HOW PARASOCIAL INTERACTION AFFECTING PURCHASE DECISION ON FASHION INDUSTRY (LOCAL BRAND) - Theresia, Astri; Dayefiandri, Aurellia; Asmarani, Kanina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The interaction happened between an individual on social media, which created the parasocial interaction often by following, liking, and interacting with the influencer on social media. They can also decide to buy products or visit the places found on the influencers' page. Thus, the influencer's credibility becomes important in terms of the effect the message transmitted to the audience. There were 105 Indonesian males and females who live in Jakarta and have bought products from the local fashion brand. This study showed the parasocial interaction between the customers and the influencers wearing the products affects purchase decisions toward local fashion brand products. The phenomenon comes from the credibility created by the influencer on their social media, the more attractive, trustworthy, and expert the influencer is, the higher the interaction created between them. Credibility becomes a factor in someone's decision-making. It also shows that they also originated the value perception toward the local fashion brand, which previously those value perceptions only appeared in the research of the luxury product.